Towards a storage system for connected homes - Gupta, Trinabh; Phanishayee, Amar; Jung, Jaeyeon; Mahajan, Ratul (Workshop on Large-Scale Distributed Systems and Middleware, 2013)
Homes are increasingly filled with connected devices such as wireless door locks, remotely controllable thermostats, and security cameras. Home automation systems, which used to be prohibitively expensive to average consumers, are now offered at an affordable price, accelerating the adoption of “smart” devices in the home. The advances in devices also enable researchers and practitioners to develop new services and applications for householders—PreHeat uses occupancy sensing to efficiently heat homes [19]; a DigiSwitch display supports elders who reside separately from their caregivers with whom they share sensed activity data in the home [5]; and a Digital Neighbourhood Watch (DNW) is proposed to help neighbors detect suspicious activities (e.g., previously unseen cars driving by several times) in the neighborhood by sharing security camera images